Effects of Fluxing Agents on Filter Aids Prepared from Lam-Dong Diatomate - Phong, Mai Thanh; Hai, Tran Duy; Tuan, Phan Dinh (ASEAN Journal of Chemical Engineering, 2012)
Diatomite (or kieselguhr) is deposit of skeletal remains of single-cell water plants (diatom algae). Diatomite can be used as raw materials for production of several products, such as filter aids, fire-bricks, adsorbents, etc. Two major deposits of diatomite in Vietnam are in Phu-Yen and Lam-Dong province. This study aims to study preparation of filter aids from Lam-Dong diatomite. Especially, the study focused on investigating effects of fluxing agents on quality of filter aids. Physic-chemical properties of the filter aids were determined by using X-ray fluorescence spectrometer, scanning electron microscope and instrumentally measured color coordinates. Results of beer filtration were also presented in this paper. The obtained results proved that Lam-Dong diatomite can be used to manufacture standard filter aids for beer filtration.